Development of Academic Atmosphere in Women's Small Enterprises in North Sumatra - Ritha Dalimunthe; Inneke Qamariah; Meutia Nauly; Rizky Putra; Siti Hafsah Hafsah Zulkarnain (Randwick International of Social Science Journal, 2023)
This community service aims to develop the academic atmosphere of women entrepreneurs to have entrepreneurial competencies in overcoming challenges and developing their enterprises to become upgraded SMEs. This service was conducted in Medan City and Deli Serdang Regency with a total of 31 women’s small enterprises. This activity was carried out using qualitative descriptive methods from 5 tools, namely documents, focus group discussions (FGDs), interviews, observations, and workshops. The results of FGDs showed that women entrepreneurs needed to collaborate with universities to make affordable and quality products. The results of interviews and observations showed that they ran the enterprises because they wanted to get more income, dared to take calculated risks, had the competence, were able to take advantage of opportunities, and were able to face changes in society. These women entrepreneurs were also given training in the form of workshops to develop the academic atmosphere and increase competence in managing entrepreneurship by creating entrepreneurial journeys, namely the understanding of being successful entrepreneurs. Therefore, they can contribute to large companies.